KAJIAN EKSPERIMENTAL PERILAKU SISTEM STRUKTUR BETON PRACETAK TERHADAP BEBAN QUASI STATIK - Hadi, Maryoko
The experimental study was conducted to investigate the behaviour of the Less Moment Connection (LMCJ precast concrete structural system, comprised of column, beam, exterior and interior beam-column joint in semi full scaled configuration. The specimen was tested under a vertical static gravity load attached on the upper-end of every column and a cyclic quasi-static horizontal load to stimulate earthquake action. The sudy was focused on the reability of the precast joint component, where the required performances of the ductility, rigidity, strength, reduction of the joint rigidity and energy disipation has been fullfilled. The results showed that the designed precast joint had a good reliable performance up to the expected ductility level, which was twice the required level. Based on the results ()phis study, it was concluded that the designed precast joint was found to have a good reliable performance which seems to have similar behavior of a conventional monolite structural concrete system, having conceptual structural design of a strong column weak beam.